A low-surface energy carbon allotrope: the case for bcc-C61. Issue 21 (7th June 2015) - Yin, Wen-Jin; Chen, Yuan-Ping; Xie, Yue-E.; Liu, Li-Min; Zhang, S. B.
<x xml:space="preserve">Abstract</x> Graphite may be viewed as a low-surface-energy carbon allotrope with little layer–layer interaction.